2016
DOI: 10.3389/fpls.2016.00014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Salt Tolerance Conferred by the Complete 2.3 kb cDNA of the Rice Vacuolar Na+/H+ Antiporter Gene Compared to 1.9 kb Coding Region with 5′ UTR in Transgenic Lines of Rice

Abstract: Soil salinity is one of the most challenging problems that restricts the normal growth and production of rice worldwide. It has therefore become very important to produce more saline tolerant rice varieties. This study shows constitutive over-expression of the vacuolar Na+/H+ antiporter gene (OsNHX1) from the rice landrace (Pokkali) and attainment of enhanced level of salinity tolerance in transgenic rice plants. It also shows that inclusion of the complete un-translated regions (UTRs) of the alternatively spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 57 publications
0
41
0
2
Order By: Relevance
“…Most of the studies involving the ectopic insertion of transgenes show some reduction in yield in abiotic stress conditions [10]. Previous studies on DST separately showed abiotic stress tolerance and enhanced yield in rice [16] [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies involving the ectopic insertion of transgenes show some reduction in yield in abiotic stress conditions [10]. Previous studies on DST separately showed abiotic stress tolerance and enhanced yield in rice [16] [20].…”
Section: Resultsmentioning
confidence: 99%
“…The disks were floated in a 20 ml solution of 150 mM NaCl for T 0 transgenic lines for 4 days at 25˚C. The analysis was carried out with three biological replicates in three independent experiments [10].…”
Section: Leaf Disk Senescence (Lds) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Pokkali maintain lower shoot Na + accumulation and lower shoot Na + /K + ratio under high salinity compared to sensitive genotypes (Kavitha et al , 2012; Sexcion et al , 2009). The enhancement of salinity tolerance by constitutive overexpression of the vacuolar Na + /H + antiporter gene from Pokkali in transgenic rice plants suggest that this landrace may use a tissue tolerance mechanism to lower shoot Na + /K + ratio under high salinity (Amin et al , 2016). Negrao et al genotyped 392 rice accessions by EcoTILLING in order to understand allelic difference for salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Use of plant dwarfism as ideal plant architecture as exemplified in the green revolution, has already reached its biological limit and has little room for improvement (Zhu et al 2010, Srinivasan et al 2017. Moreover, climate change also poses both abiotic and biotic threats, like drought, heat, salinity, sea level rise, new predatory insects, pesticide resistant pests as well as elevated level of greenhouse gases like CO 2 (Kant et al 2012, Amin et al 2016. The drastic change in the level of atmospheric CO 2 ([CO 2 ]), primarily caused by the industrial revolution which is predicted to increase by almost 50% by mid-century due to anthropogenic changes (Shimono et al 2014, Bishop et al 2015.…”
Section: Introductionmentioning
confidence: 99%